The Effects of Experience and Task – Specific Knowledge on Auditors’ Performance in Assessing A Fraud Case - Rio Tirta; Mahfud Sholihin (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2004)
The objective of this study is to investigate the relationships of auditors’ experience, knowledge, and performance. Specifically, it examined whether the task-specific knowledge variable could affect the relationship between the auditor’s experience and performance in assessing a fraud. The study hypothesized that task-specific knowledge will improve auditors’ performance in a fraud risk task. Additionally, it hypothesized that the combination of experience and fraud training would improve auditors’ performance in assessing the task. Using a sample of 64 auditors and 42 students, as expected, the study provided support for the hypotheses.Key words: Auditors’ experience; task-specific knowledge; auditors’ performance; fraud.